The Techne of Giving : Cinema and the Generous Form of Life - Campbell, Timothy C. (Book collections on Project MUSE., 2017)
"In techne of giving, Timothy Campbell elaborates a notion of generosity as way of responding to contemporary biopower. Reading films from Visconti, Rossellini, and Antonioni, he both updates their political lexicon while adopting them as models able to push back against neoliberal forms of gift-giving"--